Stranger Under Siege: Higher Education Leadership Case Study of Kennesaw State University’s Sam Olens (Iris Journal of Scholarship, 2019)
This case study and analysis explores the brief, 17-month tenure of Sam Olens as President of Kennesaw State University, including his controversial appointment, leadership mis-steps, and eventual resignation. The political and social contexts of his tenure, which coincided with political turmoil in the wake of the 2016 election and a subsequent resurgence in progressive activism throughout the country, are considered as contributing factors to his downfall. Likewise, his status as an outsider to higher education at the time of his appointment, his visibility as an outspoken conservative, and his employment being the perceived benefit of political corruption are all noted as a contributing elements to his inability to earn the confidence of the faculty and student body of Kennesaw State University, along with his divisive, misguided, and ill-conceived actions while in his executive position. The role of institutional context in regards to the recent histories of Kennesaw State University, the University System of Georgia, and the state of shared governance in American higher education as a whole are respectively explored in how they set the stage for Olens’ tumultuous and temporary reign at Kennesaw State. A set of recommended courses of action are presented as counterfactual alternatives to the events as they actually occurred, based on higher education leadership literature.
Keywords: higher education governance; higher education leadership; college president